2021
DOI: 10.1002/anie.202015960
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Modulated Reactivity: An Acidic Silane

Abstract: Compounds of main‐group elements such as silicon are attractive candidates for green and inexpensive catalysts. For them to compete with state‐of‐the‐art transition‐metal complexes, new reactivity modes must be unlocked and controlled, which can be achieved through strain. Using a tris(2‐skatyl)methylphosphonium ([TSMPH3]+) scaffold, we prepared the strained cationic silane [TSMPSiH]+. In stark contrast with the generally hydridic Si−H bond character, it is acidic with an experimental pKaDMSO within 4.7–8.1, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…It is worth pointing out that protonation causes marked geometrical changes around Si (Figure 2B), wherein the SiÀN Selected bond distances and angles are given in Section S3. [51] distances shorten from 1.840(2)-1.864 (2) BARF . No other bond in the molecule changes by > 0.02 ,a nd no flat angle deforms by > 2.98 8.I nother words,s tructural perturbations due to proton addition are mostly confined to the SiN 3 fragment.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is worth pointing out that protonation causes marked geometrical changes around Si (Figure 2B), wherein the SiÀN Selected bond distances and angles are given in Section S3. [51] distances shorten from 1.840(2)-1.864 (2) BARF . No other bond in the molecule changes by > 0.02 ,a nd no flat angle deforms by > 2.98 8.I nother words,s tructural perturbations due to proton addition are mostly confined to the SiN 3 fragment.…”
Section: Resultsmentioning
confidence: 96%
“…Displacement ellipsoids are drawn at 30 %p robability level. The BAr F 4 À counterion and hydrogen atoms, except for SiÀH, are omitted for clarity.B)Structural changes in the bicyclic cage before and after protonation accordingtoX-ray crystallography.O nly one independentm olecule of TSMPSi (1)i sshown.Selected bond distances and angles are given in Section S3 [51].…”
mentioning
confidence: 99%
“…In non-aqueous media, the p K a of a compound can be determined by a bracketing approach. 37 To this end, 3 was dissolved in THF together with equimolar amounts with a series of acids with known p K a values, and the equilibrium mixtures were analyzed by 1 H, 19 F and 31 P NMR spectroscopy. 38 Serendipitously, we found that the addition of one equiv.…”
Section: Resultsmentioning
confidence: 99%
“…[1,18,19] Neulich wurde ein zwitterionisches Silanid präsentiert, das am Siliciumzentrum ein Lewis-amphoteres Verhalten aufweist und Oxidationsstufen von + II und + IV ermöglicht, was zu einer ungewöhnlichen Reaktivität führt. [20] Wir beschrieben kürzlich das Tris(pentafluorethyl)silanid-Anion, [Si + II (C 2 F 5 ) 3 ] À , welches aufgrund seiner stark elektronenziehenden C 2 F 5 -Gruppen nicht nur als typische Lewis-Base, sondern auch als Lewis-Säure reagiert. [21] Dieser Lewis-amphotere Charakter und die Fähigkeit von pentafluorethyl-substituierten Silanen, ihre Koordinationszahl zu erweitern, machen das [Si(C 2 F 5 ) 3 ] À -Anion zu einem vielversprechenden Kandidaten für oxidative Additionen.…”
Section: Introductionunclassified
“…Ebenso vermögen Silylene auch oxidativ an starke C−X‐σ‐Bindungen (X=I, Br, Cl, F) zu addieren, wobei neutrale vierfach‐ und fünffachkoordinierte Silicium(+IV)‐Verbindungen gebildet werden (Abbildung 1). [1, 18, 19] Neulich wurde ein zwitterionisches Silanid präsentiert, das am Siliciumzentrum ein Lewis‐amphoteres Verhalten aufweist und Oxidationsstufen von +II und +IV ermöglicht, was zu einer ungewöhnlichen Reaktivität führt [20] . Wir beschrieben kürzlich das Tris(pentafluorethyl)silanid‐Anion, [Si +II (C 2 F 5 ) 3 ] − , welches aufgrund seiner stark elektronenziehenden C 2 F 5 ‐Gruppen nicht nur als typische Lewis‐Base, sondern auch als Lewis‐Säure reagiert [21] .…”
Section: Introductionunclassified